Guidelines on halal tourism management in the Andaman Sea Coast of Thailand - Chanin, Oraphan; Sriprasert, Piangpis; Abdul Rahman, Hamzah; Don, Mohd Sobri (2015)
The purposes of the research were to:1) evaluate the potential of existing Halal tourist places and to rank them; 2) examine (current) Halal tourism management practices in the Andaman Sea coast of Thailand catering for travelers from Muslim countries and; 3) propose feasible guidelines on Halal tourism management in this area.The sample groups were government officers working in the tourism-related sections, administrators in the sub-district administrative organization offices in the provinces along the Andaman Sea coast, community leaders, tour guides, officers of the provincial offices of the Islamic Council in the Andaman Sea coast, Muslim tourists from Muslim countries and officers of the Central Islamic Council of Thailand.The research instruments included a questionnaire, observations and focus group discussions.The findings suggests that Halal tourism operators must provide prayer rooms for Muslim tourists as well as the direction signs to the mosque either in English or Arabic, separate restrooms for men and women.In addition, Halal restaurants should be provided in tourist attraction areas.